Cognitive performance, sleep quality and physical activity as predictors of functional mobility in older adults - Smirni, Daniela; Tabacchi, Garden; Cottone, Roberta; Navarra, Giovanni Angelo; Muscarnera, Giulio; Di Noto, Vincenzo; Scardina, Antonino; Bellafiore, Marianna (Frontiers in Aging Neuroscience, 2025)
ObjectiveThis study investigated the relationships between functional mobility and cognitive performance, sleep quality and physical activity in older adults according to age, sex, weight status and education, and whether these variables could be predictors of functional mobility and fall risk.MethodEighty-five physically independent older adults (72.3 ± 5.67 years; 83.5% female), without significant cognitive impairments, were involved in this cross-sectional study. Functional mobility, cognitive functions as phonemic fluency, attention, memory, processing speed, and manual dexterity were, respectively, assessed with Timed Up and Go (TUG) test, phonemic fluency test, Grooved Pegboard Test, (GPT) and Symbol Digit Modalities Test, Stroop Color-Word Test. Sleep quality and physical activity were evaluated with self-reported questionnaires. Correlational and multiple regression analyses were performed.ResultsPoorer TUG performance was significantly associated with older age (ρ = 0.46, p < 0.001), lower educational level, reduced GPT performance, and lower scores on working memory, and processing speed. Age and GPT performance showed the strongest associations with TUG results. Regression analysis confirmed age and manual dexterity as significant predictors of functional mobility.ConclusionOlder age and reduced manual dexterity were linked to greater fall risk. These findings suggest that early interventions targeting fine motor skills may help preserve mobility and prevent falls in aging populations.